(untitled) (Theatrum historiae, 2006)
The period of the rule of emperor Otto III represents the new approach of the Church and Holy Roman Empire towards the newly formed states at the center of Europe. Young emperor supported various attempts to expand the Christianity together with his own influence beyond the border of his empire. Adalbert (Vojtěch), the bishop of Prague and personal Otto’s friend, played the crucial role within the new imperial eastern policy. His martyrdom in pagan Prussia stimulated numerous missions to the Central Europe heavily supported by the emperor and also by the pope. The refuge Pereon in Romagna is discussed as one of the examples of Italian roots of such missions. The location of the monastery of St. Adalbert in Pereon is described together with the main written sources as Vita beati Romualdi by Peter Damiani or Vita quinque fratrum by Bruno of Quertfurt. The place, later connected with the Camaldolian order, is completely forgotten today. The article represents one of the few remarks dealing with such missions to Central Europe from Italy early after year 1000.